Surficial sediments and post-glacial relative sea-level history, Hamilton Sound, Newfoundland - Shaw, J.; Edwardson, K. (Atlantic Geology, 1994)
Hamilton Sound is a shallow, wave-exposed cmbayment on the northeast coast of Newfoundland. Four scismostratigraphic units are recognised: (1) bedrock (acoustic basement); (2) a unit with incoherent reflections, interpreted as Late Wisconsinan glacial diamicton or till, which in places forms small drumlins; (3) a thin, acoustically stratified, draped unit found in the deepest parts of the eastern sound, interpreted as glacimarine gravelly mud; and (4) an uppermost unit with an acoustically stratified, ponded facies, and a fades which can be acoustically incoherent. Unit 4 consists of sandy mud, muddy sand, sand and gravel, and results from reworking of units 2 and 3. Three types of seabed occur (1) bedrock; (2) bouldery gravel or gravel, sub-angular to rounded, which overlies, and is derived from, glacial diamicton of acoustic unit 2. The coralline alga Lilholhamnion sp. coats some clasts on their upper surfaces and some clasts completely. This, together with the occurrence of gravel ripples in several areas, is evidence of intermittent sediment mobility, and (3) gravelly sand, sand, muddy sand, or sandy mud, located in basins. Seabed features in this zone include dunes, iceberg furrows and pits. The regional relative sea-level curve is constrained by two types of morphological evidence: rounded drumlin crests at depths below 19 m which would have been truncated if sea level had fallen below -18.S m, and (wave-cut) terraces at depths of 17 to 21 m. These data are indicative of a -17 m lowstand of relative sea level. Radiocarbon dates from a vibracore suggest that the lowstand occurred prior to 8.6 ka B.P. During the lowstand Fogo Island was connected to the mainland by a narrow isthmus.